EXAMINING THE RELATIONSHIP BETWEEN LIVABILITY AND SUBJECTIVE WELL-BEING IN SHAPING THE QUALITY OF LIFE OF INDIGENOUS COMMUNITIES: EVIDENCE FROM PAMPANG CULTURAL VILLAGE, INDONESIA - Nur Anizah Mulky; Nurul Kamaliah Umasangaji (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the livability and subjective well-being of the Dayak Kenyah community in Pampang Cultural Village, Samarinda City, East Kalimantan, Indonesia. The study is motivated by the growing attention to quality of life, which is no longer assessed solely through economic and infrastructural dimensions but also through environmental comfort, social relationships, cultural identity, and subjective well-being. A qualitative approach with a phenomenological design was employed to explore community members’ lived experiences and interpretations of their residential environment and perceived well-being. Data were collected through semi-structured interviews, field observations, and documentation. Informants were selected purposively and consisted of local residents, customary leaders, and village officials who possessed relevant knowledge and experience regarding the phenomenon under investigation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings reveal that the livability of Pampang Village is shaped by a comfortable residential environment, relatively adequate access to basic facilities, a high level of security, strong social cohesion, and the sustainability of Dayak Kenyah cultural traditions. Meanwhile, the community’s subjective well-being is reflected in high levels of life satisfaction, happiness, gratitude, and pride in their cultural identity. The study further demonstrates that quality of life is constructed through the interaction between a livable environment, social capital, and the continuity of local cultural values. This research contributes to the advancement of livability and subjective well-being studies within the context of indigenous communities and provides practical implications for the formulation of development policies that emphasize community welfare, cultural preservation, and environmental sustainability.